1987
DOI: 10.1038/bjc.1987.294
|View full text |Cite
|
Sign up to set email alerts
|

Tumour necrosis factor in man: Clinical and biological observations

Abstract: Summary Eighteen patients with advanced cancer have been treated intravenously with human recombinant tumour necrosis factor (rhTNF). The drug produced febrile reactions at all doses although these were preventable by steroids and indomethacin. Doses at or above 9 x 105 units (400 pg)m-2 were associated with hypotension, abnormal liver enzymes, leucopenia and mild renal impairment in a substantial proportion of patients. RhTNF was cleared from plasma with a half life of -20 minutes but non-linear pharmacokinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
73
2
2

Year Published

1989
1989
2008
2008

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 198 publications
(82 citation statements)
references
References 27 publications
5
73
2
2
Order By: Relevance
“…(2 . Most studies with cancer patients have also reported undetectable serum levels of TNF (Selby et al, 1987), even in patients that had lost eight to 40% of their pre-morbid weight (Socher et al, 1988). Two studies have, however, reported elevated serum levels of TNF, one in children with malignancy (Saarinen et al, 1990), and another in cancer patients with active disease (Balkwell et al, 1987) .…”
Section: Mechanism Of Cachexiamentioning
confidence: 99%
“…(2 . Most studies with cancer patients have also reported undetectable serum levels of TNF (Selby et al, 1987), even in patients that had lost eight to 40% of their pre-morbid weight (Socher et al, 1988). Two studies have, however, reported elevated serum levels of TNF, one in children with malignancy (Saarinen et al, 1990), and another in cancer patients with active disease (Balkwell et al, 1987) .…”
Section: Mechanism Of Cachexiamentioning
confidence: 99%
“…Large studies are currently underway but, for the time being, no consensus has emerged from preliminary results concerning the clinical efficacy of this lymphokine in the treatment of malignancy, little evidence of TNF anti-tumour activity having been observed in vivo. Although partial remissions were documented in individual patients with colon and pancreatic cancer and B cell lymphomas, only a few clinically significant benefits have been observed (Blick et al, 1987;Creaven et al, 1989;Herrmann, 1989;Moritz et al, 1989;Selby et al, 1987;Sherman et al, 1988) One of the most promising approaches is represented by the use of TNF in association with other interleukins, and in particular with IL-2 since a synergism occurs between TNFalpha and IL-2 in the generation of lymphokine activated killer (LAK) cells (Chouaib et al, 1988;Owen-Schaub et al, 1988;Matossian-Rogers et al, 1989;Yang et al, 1989). The interaction between IL-2 and TNF on LAK precursors results in a reduction of the IL-2 concentration required for the differentiation of granular lymphocytes into LAK cells.…”
Section: Diseases In Which An Increase Of Tnf Has Been Foundmentioning
confidence: 99%
“…Glycogenolysis and lipolysis, proteolysis and gluconeogenesis are some of the metabolic events that may cause a profound nutritional insult to this group of patients (Moldawer et al, 1987;Fong et al, 1990;Falconer et al, 1994). The role of TNF in patients with cancer is not entirely clear, as some researchers report that no correlation exists between TNF concentrations and the severity of malnutrition (Balkwill et al, 1987;Selby et al, 1987). Furthermore, not all of the researchers agree about the changes in energy expenditure in children with malignancies.…”
Section: Indications For Bone Marrow Transplantation As Determinants mentioning
confidence: 99%